2018
DOI: 10.1021/acsphotonics.8b01083
|View full text |Cite
|
Sign up to set email alerts
|

Förster Resonance Energy Transfer inside Hyperbolic Metamaterials

Abstract: The ability to control Förster Resonance Energy Transfer (FRET) between emitters via the design of nanostructured materials with appropriate electromagnetic properties is important in the development of fast and enhanced sources of illumination, high-efficiency photovoltaic devices and biomedical applications, such as nanorulers. While the engineering of the local density of states allows an efficient control over the spontaneous emission rate, its influence on the FRET process has been an ongoing debate and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Then, in Figure 5(b) we see that the FRET efficiency is almost constant for large nanopore sizes (30% and 31%), and then it increases as the size of the nanopore shrinks. Despite the fact that the distance between the dyes is not constant, the efficiency values obtained are comparable to those obtained by some other groups using similar structures 22 . The efficiency vs size behaviour is also quite intuitive: we assume that the dyes are attached onto the wall of the nanopore at a constant rate.…”
Section: -Top Panel)supporting
confidence: 85%
“…Then, in Figure 5(b) we see that the FRET efficiency is almost constant for large nanopore sizes (30% and 31%), and then it increases as the size of the nanopore shrinks. Despite the fact that the distance between the dyes is not constant, the efficiency values obtained are comparable to those obtained by some other groups using similar structures 22 . The efficiency vs size behaviour is also quite intuitive: we assume that the dyes are attached onto the wall of the nanopore at a constant rate.…”
Section: -Top Panel)supporting
confidence: 85%
“…Several contributions have explored the influence of nanophotonics for FRET using microcavities, 18,[22][23][24] mirrors, [25][26][27][28][29] nanoparticles, [30][31][32][33][34][35][36][37] nanoapertures, [38][39][40][41][42][43][44] nanoantennas, [45][46][47][48][49] waveguides, 50 or hyperbolic metamaterials. 51,52 However, none of these works has clearly demonstrated experimentally the enhancement of the smFRET detection range in the near field. Actually, most cases consider short donor-acceptor separations (on the order or below the Förster radius) in order to ease the optical detection.…”
mentioning
confidence: 99%
“…Actually, most cases consider short donor-acceptor separations (on the order or below the Förster radius) in order to ease the optical detection. 23,25,36,37,46,47,52 It should be acknowledged that long range energy transfer over distances up to several micrometers has been reported, [53][54][55][56][57][58] but these studies are based on radiative dipole-dipole coupling (i.e. energy transfer mediated by a propagating photon or plasmon in the far field).…”
mentioning
confidence: 99%
“…Most of the experimental studies involving hyperbolic metamaterials reported Purcell factors of several tens, reaching ≈80 with additional structuring of a metal‐dielectric multilayer metamaterial . In nanorod‐based hyperbolic metamaterials, decay rate enhancements of dipolar emitters reaching up to 100 were observed, depending on the positioning of the emitters in the unit cell as well as the material losses, and led to emission in both free space and waveguided modes of the metamaterial slab …”
Section: Introductionmentioning
confidence: 99%
“…[16] In nanorod-based hyperbolic metamaterials, decay rate enhancements of dipolar emitters reaching up to 100 were observed, depending on the positioning of the emitters in the unit cell as well as the material losses, [9] and led to emission in both free space and waveguided modes of the metamaterial slab. [15,17] Spontaneous emission from other atomic transitions has, however, not been extensively investigated, mostly due to their conventionally forbidden character strictly controlled by selection rules. Electric-dipole-forbidden atomic transitions, such as magnetic-dipole transitions, multipolar transitions with orbital angular momentum changes, spin-flip-required, or singlettriplet transitions, are typically orders of magnitude slower than regular dipolar transitions between selection-rule-allowed states, and therefore are hardly experimentally observable.…”
Section: Introductionmentioning
confidence: 99%